Charakterizace inhibičních vlastností proteinu TbIF1 vůči mitochondriálnímu komplexu F1-ATPázy u bičíkovce Trypanosoma brucei. - Váchová, Hana (Jihočeská univerzita, 2013)
To map and define the minimal inhibiting sequence of the inhibitory peptide TbIF1 and to improve its inhibiting property, a series of the N- and C- terminal truncations of TbIF1 was created. The mutated recombinant TbIF1 his-tagged proteins were over-expressed and purified from the E.coli cells and their binding and inhibiting properties were tested using purified F1-ATPase complex.
Inhibiting properties of the inhibitory protein TbIF1 to T. brucei F1-ATPase.